1990
DOI: 10.1007/bf01054983
|View full text |Cite
|
Sign up to set email alerts
|

Predicting bioaccumulation potential: A test of a fugacity-based model

Abstract: Clams (Macoma nasuta) from an unpolluted site in Yaquina Bay, Oregon were exposed in the laboratory for 28 days to 6 field-contaminated sediments (treatments) which varied widely in concentration of 10 organic pollutants. Mean accumulation factors (AF = (concentration in tissue/lipid, %/100)/(concentration in sediment/total organic carbon, %/100] of 8 neutral organic compounds (DDE [p,p'], 2,2',3,5'6-pentachlorobiphenyl, 2,3',4,4',5-pentachlorobiphenyl, Aroclor 1254, pyrene, chrysene, benzo[a]pyrene, benzo [b,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
5

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
5
33
5
Order By: Relevance
“…An additional study by Drouillard et al (2008) For N. virens, the 28-d and steady-state BSAFs were similar among congeners and between the Arthur Kill and Newark Bay sediment exposures ( Figure 16). The BSAFs obtained in this study were lower overall compared to previously reported values (0.19-1.41) (Pruell et al 1993 Ferraro et al 1990Ferraro et al , 1991Brannon et al 1993;Pruell et al 1993;Boese et al 1995Boese et al , 1996. Overall, the BSAFs obtained in this study for M. nasuta were lower compared to previously reported values.…”
Section: Polychlorinated Biphenyls (Pcbs)contrasting
confidence: 87%
See 2 more Smart Citations
“…An additional study by Drouillard et al (2008) For N. virens, the 28-d and steady-state BSAFs were similar among congeners and between the Arthur Kill and Newark Bay sediment exposures ( Figure 16). The BSAFs obtained in this study were lower overall compared to previously reported values (0.19-1.41) (Pruell et al 1993 Ferraro et al 1990Ferraro et al , 1991Brannon et al 1993;Pruell et al 1993;Boese et al 1995Boese et al , 1996. Overall, the BSAFs obtained in this study for M. nasuta were lower compared to previously reported values.…”
Section: Polychlorinated Biphenyls (Pcbs)contrasting
confidence: 87%
“…The BSAF values were substantially lower for the Arthur Kill sediment except for fluoranthene (Table C4; Figure 26), consistent with similar data determined for PCBs. The BSAF values determined for the Newark Bay site were similar to values reported by Ferraro et al (1990).…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)supporting
confidence: 86%
See 1 more Smart Citation
“…A recently developed steady-state partitioning model for bioaccumulation of sediment-associated neutral organics This normalization reduces the variability in BAF values among sediments and organisms [18,. Some authors have used "preference factors," the inverse of AFs [17,20], but AFs are more readily understood as a result of their direct relationship to BAFs.…”
Section: Steady-state Modelsmentioning
confidence: 99%
“…BSAFs have also been used to compare bioaccumulation across different species and sites, which is further based on the assumption that these factors are independent of species, type of sediment, organic carbon, and contaminant. The present study, and work by others, suggests that these assumptions are not always valid [5,9,16,[29][30][31][32]. Indeed, it has been shown that different fractions of TOC, black carbon in particular, can enhance sorption and decrease bioavailability of contaminants, especially with planar compounds such as PAHs or PCDD/Fs [33][34][35].…”
Section: Comparison: Laboratory and Field Methodsmentioning
confidence: 66%